VOLKMANN’S ISCHAEMIC CONTRACTURE FOLLOWING DELAYED ANTIVENOM ADMINISTRATION: A CASE REPORT - Ramesh Muthu; Kaneson, Surekha (International Journal of Allied Health Sciences, 2019)
Snake envenomation is a serious health problem in Malaysia; however, it rarely causes compartment syndrome directly. Local envenomation will result in swelling, blistering and necrosis, while systemic envenomation will result in bleeding diathesis, hypotension and shock. Specific antivenom is required to reverse the symptoms of progressive oedema, coagulopathy and tissue necrosis, nevertheless delayed and inappropriate anti-venom may prove devastating. We reported a case of king cobra (Ophiophagus hannah) bite on a patient who developed compartment syndrome. Even though fasciotomy and debridement have been performed, the patient still developed a complication of Volkmann Ischaemic Contracture (VIC).